Chitosans and Nanochitosans: Recent Advances in Skin Protection, Regeneration, and Repair - Patricia Garcia Ferreira; Vitor Francisco Ferreira; Fernando de Carvalho da Silva; Cyntia Silva Freitas; Patricia Ribeiro Pereira; Vania Margaret Flosi Paschoalin (MDPI AG, 2022)
Chitosan displays a dual function, acting as both an active ingredient and/or carrier for pharmaceutical bioactive molecules and metal ions. Its hydroxyl- and amino-reactive groups and acetylation degree can be used to adjust this biopolymer's physicochemical and pharmacological properties in different forms, including scaffolds, nanoparticles, fibers, sponges, films, and hydrogels, among others. In terms of pharmacological purposes, chitosan association with different polymers and the immobilization or entrapment of bioactive agents are effective strategies to achieve desired biological responses. Chitosan biocompatibility, water entrapment within nanofibrils, antioxidant character, and antimicrobial and anti-inflammatory properties, whether enhanced by other active components or not, ensure skin moisturization, as well as protection against bacteria colonization and oxidative imbalance. Chitosan-based nanomaterials can maintain or reconstruct skin architecture through topical or systemic delivery of hydrophilic or hydrophobic pharmaceuticals at controlled rates to treat skin affections, such as acne, inflammatory manifestations, wounds, or even tumorigenesis, by coating chemotherapy drugs. Herein, chitosan obtention, physicochemical characteristics, chemical modifications, and interactions with bioactive agents are presented and discussed. Molecular mechanisms involved in chitosan skin protection and recovery are highlighted by overlapping the events orchestrated by the signaling molecules secreted by different cell types to reconstitute healthy skin tissue structures and components.